Effect of Different Types of Biochar Application on Secondary and Micronutrients Content and Uptake by Fodder Maize - Yadav, Naresh K.; Kumar, Rajkishore; Bishnoi, Subodh K.; Patel, P. C. (International Journal of Bio-resource and Stress Management, 2015)
An investigation was carried out to study the effect of three biochar applications viz., maize stover (MS), cluster bean stover (CB) and Prosopis julifera wood (PJ) and one farm yard manure (FYM) on secondary and micronutrients content and uptake by fodder maize during 2010-11 and 2011-12. The biochar and FYM both were applied @ 5 t and 10 t ha-1. The recommended dose of fertilizer (RDF) (80-40-0 kg ha-1 N-P-K) was applied in eight treatments and remaining eight treatments comprised of biochar and FYM. The Zn and Fe were applied in form of ZnSO4 @ 20 kg ha-1 and FeSO4 @ 40 kg ha-1, respectively in all treatments as basal. There was a significant increase in the S and Mn concentration with the application of CB biochar @ 5 t ha-1 without RDF and with RDF significantly increased the Mg concentration in maize. Application of PJ biochar @ 5 t ha-1 along with RDF significantly increased Ca, Zn and Fe concentration and FYM @ 5 t ha-1 along with RDF resulted in the highest Cu concentration in maize. Nutrient uptake like Ca, Mg, S, Cu, higher removals of Zn and Fe in maize and highest available Ca and Mg content were significantly increased with the application of RDF+MS10 while the uptake of Mn and DTPA extractable Zn, Cu, Mn and Fe content in soil were significantly increased with the application of RDF+MS5. CB biochar @ 10 t ha-1 along with RDF showed significantly the highest available S content in soil.